Technical and Economic Analysis of Efficiency of Electronic Means’ Quality Management - I. Gorobets, A.; S. Novikov, A.; Yu. Cheremukhina, Yu.; A. Nazarenko mirea, M. (International Journal of Engineering and Technology, 2018)
The requirements for quality assurance of technical and economic analysis of the effectiveness of electronic means at different stages of the life cycle are considered.Â